1993
DOI: 10.1063/1.465516
|View full text |Cite
|
Sign up to set email alerts
|

Influence of retardation on the higher-order multipole dispersion contributions to the helium dimer potential

Abstract: In this note, we evaluate the influence of the relativistic retardation corrections on the dipole–quadrupole, dipole–octupole and quadrupole–quadrupole contributions to the He–He dispersion potential, which affect the attractive r −8 and r −10 terms. These higher-order corrections influence the binding energy of 4He2 an order of magnitude less than does the retardation correction to the leading r −6 dipole–dipole term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In many applications it is necessary to relax the electric dipole approximation and include the effects of higher‐multipole moment terms. Well known cases where electric quadrupole and electric octupole contributions need to be accounted for to improve the accuracy of the interaction energy include the helium dimer and pairs of alkali metal atoms . To correctly treat discriminatory dispersion forces that manifest in interactions between chiral molecules, the effects of magnetic dipole and electric quadrupole couplings must be accounted for.…”
Section: Effects From Fluctuations Of the Vacuum Electromagnetic Fieldmentioning
confidence: 99%
“…In many applications it is necessary to relax the electric dipole approximation and include the effects of higher‐multipole moment terms. Well known cases where electric quadrupole and electric octupole contributions need to be accounted for to improve the accuracy of the interaction energy include the helium dimer and pairs of alkali metal atoms . To correctly treat discriminatory dispersion forces that manifest in interactions between chiral molecules, the effects of magnetic dipole and electric quadrupole couplings must be accounted for.…”
Section: Effects From Fluctuations Of the Vacuum Electromagnetic Fieldmentioning
confidence: 99%
“…The first several electric multipole results of Au and Feinberg (1972) were used for applications to calculations of the binding energy of the helium dimer by Luo et al (1993) and by Chen and Chung (1996) and for applications to ultracold atom scattering by Marinescu et al (1994), who evaluated the expressions for a pair of hydrogen atoms and for a pair of like alkali-metal atoms.…”
Section: Two Atomsmentioning
confidence: 99%
“…Other systems in which electric quadrupole and octupole moments play a significant role include the dispersion force between two hydrogen atoms, two helium atoms, and alkali–metal pairs. Previous computations 1, 5, 13 of the van der Waals potential in these latter systems have shown that including higher multipole moments, as well as the effect of retardation (which is crucial at large separations), can lead to a significant lowering of the binding energy—by up to 10% in the case of the helium dimer. For intermolecular interactions between chiral molecules 2, 7, 10, however, it is necessary to include magnetic dipole interaction terms in the coupling Hamiltonian in addition to electric dipole ones for a proper description.…”
Section: Introductionmentioning
confidence: 99%